Combining beams in different locations for aerospace defense in a turbulent atmosphere - Liao, Kangjie; Liu, Zhiwei; Chu, Xiuxiang (Frontiers in Physics, 2022)
A fixed high-power laser system used as an aerospace defense weapon has limitations such as the transmitter size, serious thermal blooming during propagation, rapid motion, and the variation of the location of the target. In the present paper, we propose a method by arranging many high-power systems with adequate distance in a defense area. The intensity distribution and the energy irradiated on the target are studied and compared with a fixed laser system. Results show that adequate arrangement of many high-power laser systems can reply to the arbitrary and rapid motion of the target.